Numerical Analysis of Seat Inclination Effect on Student Chair Structural Performance Using Finite Element Method - Taufik Ramadhan Fitrianto; Bahtiar Rahmat; Nurhanifah Nurhanifah; Siska Anggiriani; Desy Mulyosari; Alfani Risman Nugroho (Infotekmesin, 2026)
Student chairs are commonly designed based on ergonomic dimensions without considering the structural implications of seat configuration. This study investigates the effect of seat inclination on the structural response of a mahogany student chair using the Finite Element Method (FEM). Two anthropometrically derived chair models—a flat seat and a 4° inclined seat—were developed based on student anthropometric data from the Polytechnic of Furniture and Wood Processing Industry Kendal. Static simulations were performed in Autodesk Inventor 2022 under a 2000 N vertical seat load and an additional backrest load equivalent to 40% of the seat load. Structural performance was evaluated using Von Mises stress, total deformation, and Factor of Safety (FoS). The flat-seat model produced a maximum stress of 16.94 MPa, a deformation of 1.118 mm, and a FoS of 2.755, whereas the 4° inclined-seat model yielded 23.25 MPa, 1.501 mm, and 2.007, respectively. Although the inclined seat increased stress concentration and deformation, both configurations remained structurally safe, indicating that a 4° seat inclination represents an acceptable trade-off between ergonomic improvement and structural reliability.